Do patients know their post-operative plan? A prospective cohort study of orthopaedic trauma patients at a level I trauma center. Issue 6 (June 2021) - Jester, Adam; Ruland, Christoper; Paryavi, Ebe; Zerhusen, Tim; Butler, Bennet; O'Toole, Robert V.
Abstract: Objective: Patient compliance with weight bearing and physical therapy recommendations is critical following an orthopedic injury. Proper compliance requires knowledge of the postinjury plan, but there is little published data regarding comprehension of postinjury recommendations among orthopedic trauma patients. We hypothesized that patient knowledge of weight bearing and physical therapy instructions following an orthopaedic injury would be poor. Design: Prospective Observational Cohort Setting: Level I Trauma Center Patients: 194 prospectively enrolled patients completed a questionnaire testing their knowledge of their weight bearing status and physical therapy plan at their first clinic visit following an inpatient admission with an orthopedic injury Results: Despite the fact that 73% of patients were participating in physical therapy following hospital discharge, only 66% (95% CI 60–73%) of patients correctly identified their postinjury weight bearing status. A multivariate analysis found no significant correlation between chance of knowing postoperative weightbearing status or physical therapy plan and any of the socioeconomic patient factors we collected. Conclusions: Orthopedic trauma patients had a relatively poor understanding of even basic postinjury physical therapy instructions. This did not appear to be affected by age, gender, or socioeconomic factors. Orthopedic trauma surgeons should be aware of the significant potential for knowledge deficits among their patients and should make specific efforts to identify and correct those deficits.